Movement of Zimbabwean immigrants into, within and out of the farm labour market in Limpopo province of South Africa - Kudejira, Denboy (University of the Western Cape, 2019)
Magister Philosophiae (Land and Agrarian Studies) - MPhil(LAS) === This thesis presents findings from ethnographic research conducted over a period of 17 months in the Blouberg and Molemole local municipalities of Capricorn District in Limpopo province with the aim of exploring mobility patterns of Zimbabwean migrants into, within and out of the South African farm labour market, and understanding how these movements are linked to access to food and other livelihood opportunities. Limpopo serves both as a transit province for Zimbabweans who wish to proceed further south to other provinces of South Africa and a destination for irregular migrants who live and work on white-owned commercial farms. Although constrained mobility, which results from their illegality and remoteness of farms from public services, limit their access to sources of food, irregular Zimbabwean migrants in Blouberg-Molemole area perceive that moving into South African farm labour has improved their food security and livelihood statuses. The South Africa farm labour market provides opportunities to earn income, and enables them to make long term investments in their families back home above immediate individual food security needs. Horizontal and vertical social networks established among Zimbabwean migrants in the Blouberg-Molemole area do not only serve the purpose of facilitating information sharing, but are also forms of social capital on which individual members depend on for their food security and livelihood needs.